Effect of Pretreatment with Low-Frequency Ultrasound on Quality Parameters in Gulupa (Passiflora edulis Sims) Pulp (2021)
The Gulupa (Passiflora edulis f. edulis Sims) is an expression of South America’s tropics’ biodiversity, and a source of B vitamins and amino acids. It is a climacteric export fruit for which it is necessary to incorporate emerging technologies for its conservation and transport. This work investigated the effect of ultrasound on gulupa pulp and verified the stability of the characters of interest in the shelf life of 20 days. Six treatments and a control sample were used, evaluated in triplicate, and varied in frequency (30 and 40 kHz) with an exposure time of 10, 20, and 30 min. A statistical analysis of unidirectional variances and Dunnett’s test was used. It was found that the ultrasound treatments did not affect the pH or the titratable acidity. Soluble solid results presented a significant increase (p < 0.05) (from 13.4 to 14.8% w/v) in the antioxidant capacity (from 1.13 to 1.54 µmol Trolox Equivalent (TE)/g by the ABTS•+ (2,20 -azino-bis(3-ethylbenzothiazoline-6-sulfonic acid)) Cationic Radical Assay and from 3.3 to 3.7 µmol TE/g by the DPPH· (2,2-diphenyl-1-picrilhydrazil) Radical Scavenging Assay). During the shelf life, ascorbic acid was the parameter that varied most (p < 0.05). It decreased from 42.7 to 21.6 mg ascorbic acid/100 g of pulp in the control sample. However, a smaller decrease was observed (23.8–24.5 mg ascorbic acid/100 g of pulp) in the 40 kHz treatments. The smallest global color difference (∆E) for the control was found in the 40 kHz treatment at 30 min through the entire shelf life (day 0 to 20). Ultrasound treatment offers a new strategy to improve and extend the shelf life of chilled gulupa pulp.